Factors affecting occupational burnout in medical staff: a path analysis based on the job demands-resources perspective - Wei, Zuolin; Xia, Bocheng; Jiang, Lingli; Zhu, Huaiyi; Li, Lingyan; Wang, Lin; Zhao, Jun; Fan, Ruoxin; Wang, Peng; Huang, Mingjin (Frontiers in Psychiatry, 2024)
To assess occupational burnout conditions and work-related factors among frontline medical staff during the COVID-19 pandemic and analyse the relationships among these factors utilizing the job demands-resources (JD-R) model as a theoretical framework. Methods: An online survey was distributed to medical staff in one city via convenience sampling during 12/29/2022-1/10/2023. Path analysis was utilized to explore the relationship between work-related factors and occupational burnout among frontline medical staff during the COVID-19 outbreak.Results:Among 474 respondents, 455 frontline medical staff (female=79.56%) were included in the final analysis. Medical staff aged <35 exhibited higher levels of occupational burnout than did older staff. Depression/anxiety and workload were positively correlated with occupational burnout and negatively correlated with self-compassion, workplace health/safety, and workplace support. Path analysis indicated the direct effects of workplace support, depression/anxiety, workplace health/safety, self-compassion, and workload on occupational burnout. There were also partial mediating effects of workplace support, depression/anxiety, workplace health/safety, and self-compassion on occupational burnout. The model demonstrated good fit. Conclusion: Workplace support, a crucial job resource, can improve occupational burnout among frontline medical staff in various ways. Reducing anxiety, depression, and workload and improving workplace support, health/safety, and self-compassion are practical and effective measures for mitigating occupational burnout.